2022
DOI: 10.1002/pri.1981
|View full text |Cite
|
Sign up to set email alerts
|

Effects of telehealth on functional capacity, mental health and quality of life among older people with dementia: LAPESI telehealth protocol for a randomized controlled trial

Abstract: Background Telehealth can be an alternative action at a distance that can help as a form of motor intervention, alleviating the deleterious effects arising from social distancing on functional capacity, mental health and quality of life among older people with dementia during the COVID‐19 pandemic. Purpose We aim to analyze the effects of a telehealth program on functional capacity, mental health and quality of life among older people with dementia and their caregivers. Methods seventy‐eight individuals with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…This is a cross-sectional study undertaken as a secondary analysis from a randomized clinical trial 18 previously carried out by our laboratory. Seven hundred and forty-two volunteers were recruted through advertisements placed in newspapers, online magazines, and social media, as well as telephone contact via the database of the UFSCar Research and Health of Older People Laboratory; however, only 43 met the inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…This is a cross-sectional study undertaken as a secondary analysis from a randomized clinical trial 18 previously carried out by our laboratory. Seven hundred and forty-two volunteers were recruted through advertisements placed in newspapers, online magazines, and social media, as well as telephone contact via the database of the UFSCar Research and Health of Older People Laboratory; however, only 43 met the inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Strategies based on the practice of physical exercises are effective in improving functional ability, mental health, and quality of life. For example, Tsen et al (2023) showed that telehealth (i.e., instructions at a distance to practice exercise) improved physical capacity, mental health and quality of life of elderly with dementia, reducing the deleterious effects arising from social distancing on during the COVID-19 pandemic. (Tsen et al, 2023).…”
Section: Fernandes Et Almentioning
confidence: 99%
“…For example, Tsen et al (2023) showed that telehealth (i.e., instructions at a distance to practice exercise) improved physical capacity, mental health and quality of life of elderly with dementia, reducing the deleterious effects arising from social distancing on during the COVID-19 pandemic. (Tsen et al, 2023). Regular physical activity is known to have a protective effect, not only preserving but often enhancing physical functionality and strength in elderly (Cress et al, 1999).…”
Section: Fernandes Et Almentioning
confidence: 99%
“…This research is part of a randomized clinical trial in collaboration between researchers from Brazil and Australia, named: "Telerehabilitation as an alternative to the COVID-19 pandemic and its effects on the functional capacity, mental health, and quality of life of older individuals with dementia: a randomized controlled clinical trial" (Registration: RBR-825p57 vwv). Further information can be obtained in the study protocol 15 .…”
Section: Designmentioning
confidence: 99%
“…Recruitment was conducted through digital media and distribution of pamphlets in physical locations, resulting in a total of 41 caregivers and 41 older individuals with dementia. The exclusion and inclusion criteria are described in the study protocol 15 .…”
Section: Population and Samplementioning
confidence: 99%